Long run dynamics of regional growth in Chile - Oyarzún, Carlos; Araya, Ivan (Estudios de Economía, 2016)
The aim of this article is to examine the process of economic growth in the regions of Chile using a time series approach.In particular,we test the hypothesis of a unit root in the log of the ratios of per capita product between every possible pair taken from the 13 regions.The ‘acceptance’ of the null hypothesis means that the ratio of the per capita product doesn’t tend to revert to a deterministic constant value and therefore,one of the definitions of convergence in Bernard and Durlauf (1996) is violated.We have found that there are two groups of regions that show within-group convergence but the two groups don’t converge. Also,there are two regions that don’t converge with any other region of the country.